How Will Collaboration With CCAFS Help Improve Work With Poor Indian Farmers? - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Interview with Tamali Kundu from PRADAN, India. Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya